Pengaruh Gaya Kepemimpinan, Kompensasi Finansial terhadap Motivasi Studi pada Karyawan PT. Sumekar Line BUMD Sumenep - Ach Syarif Walid Hujairi; Faidal Faidal (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This study discussed the problems in PT. Sumekar Line Sumenep. Those are the  leadership style, financial compensation that have effect on employees motivation. So, there are 3 variables: Leadership Style, Financial Compensation and (Employees) Motivation. It uses a quantitative approach, and an analytic observational styles. The number of respondents are 54. The purposes are to determine the effect of Leadership Style and Financial Compensation on Motivation. Using this analysis (multiple linear regression), the results showed that the Leadership Style and Financial Compensation have effect on Motivation partially and simultaneously. It included: 1). The Leadership Style has a positive and significant effect on the Motivation, the tcount is 2.831 ttable  is 2.007 and the significant level is 0.007 0.05; 2). The Financial Compensation has a positive and significant effect on the Motivation, the tcount is 4.178 ttable is 2.007 and the significant level is 0.000 0.05;  3). The Leadership Style and Financial Compensation have a positive and significant effect on the Motivation at PT. Sumekar Line Sumenep as a significant level is 0.000 0.05, the Fcount is 32.485 ˃ Ftable is 3.18.